Mangrove Forest Management and Mangrove-Based Business Development Opportunities in the Gulf of Prigi Trenggalek - Purwanti, Pudji; Susilo, Edi; Lestariadi, Riski Agung (Institute of Research and Community Service, University of Brawijaya, 2017)
The mangrove forests in the Prigi Gulf located in Damas beach and Cengkrong beach. In one decade, the mangrove forest area has decreased quite dramatically. The decreasing is the result of land conversion activities as oil plantations. This study aimed to describe the management of mangrove forests, the identifying mangrove vegetation, and analyze the mangrove-based business opportunities that can be developed.Mangrove fruit actually can be used as syrup’s ingredient. But it’s at an early stage. In order to reduce the destruction of forests mangrove, several things as introduces mangrove functions as coastal life support and mangrove benefit directly as a material that can be developed for productive business. Based on the data, mangrove can be used for making some product such as batik, brownies and crackers. Feasibility analyses show that batik mangrove have an NPV value of Rp. 73,101,417, IRR 352.79%, Net B/C 19.93 and Pay Back Period 0.8. Brownies has a value of Rp 8,413,444 NPV, IRR 29.01%, Net B / C 1.78 and Pay Back Period 3.18. Crackers have a value of Rp 8,094,869 NPV, IRR 62.21%, Net B / C 3.54 and 1.59 Pay Back Period. Based on these values, the mangrove processing business is feasible and can be developed for productive business.Keywords: land use, mangrove-based business feasibility